2023
DOI: 10.1108/qram-09-2022-0135
|View full text |Cite
|
Sign up to set email alerts
|

The future of public sector accounting research. A polyphonic debate

Abstract: Purpose The purpose of this polyphonic paper is to report on interdisciplinary discussions on the state-of-the-art and future of public sector accounting research (PSAR). The authors hope to enliven the debates of the past and future developments in terms of context, themes, theories, methods and impacts in the field of PSAR by the exchanges they include here. Design/methodology/approach This polyphonic paper adopts an interdisciplinary approach. It brings into conversation ideas, views and approaches of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 200 publications
(283 reference statements)
0
26
0
2
Order By: Relevance
“…Issues of financial accountability and transparency of governments when facing such crises have led to more scholarly attention. To what extent such transparency and accountability can be restored through the adoption of international public sector accounting standards is a key question (Grossi et al, 2023;Van Helden et al, 2021;Polzer et al, 2019Polzer et al, , 2022. Whilst a few studies (Tawiah, 2023;Tawiah and Soobaroyen, 2022), as well as the reports published by international organisations and the accounting profession (Khan and Mayes, 2009;ACCA, 2017), outline several benefits that emerging economies can derive from IPSAS-based reporting, a paper by Polzer et al (2023) (in this special issue) has charted the different cultural, structural and economic constraints in the implementation process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Issues of financial accountability and transparency of governments when facing such crises have led to more scholarly attention. To what extent such transparency and accountability can be restored through the adoption of international public sector accounting standards is a key question (Grossi et al, 2023;Van Helden et al, 2021;Polzer et al, 2019Polzer et al, , 2022. Whilst a few studies (Tawiah, 2023;Tawiah and Soobaroyen, 2022), as well as the reports published by international organisations and the accounting profession (Khan and Mayes, 2009;ACCA, 2017), outline several benefits that emerging economies can derive from IPSAS-based reporting, a paper by Polzer et al (2023) (in this special issue) has charted the different cultural, structural and economic constraints in the implementation process.…”
Section: Discussionmentioning
confidence: 99%
“…Participatory and political processes of deliberation have, therefore, been at the centre of public sector accounting to identify what counts as "value" and "valuable" from a societal perspective. The view that public sector accounting should provide a medium through which to define, express and represent public value has also been highlighted in the work by Grossi et al (2023). Steccolini (2019) also contends that public sector accounting now intersects with a multiplicity of disciplines, sectors, professions, interests and powers and that the wider social significance of public sector accounting has been well acknowledged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, international organizations such as the World Bank have received significant scholarly attention, particularly in the context of the adoption of public sector accounting technologies by emerging economies. However, Grossi et al (2023) argue that government accounting systems framed by market-driven principles do not guarantee their successful implementation in emerging economies. In this scholarly landscape, this field study underscores the need to shift the focus to state-driven financial systems, as exemplified by the Korean government financial information system when recipient countries consider adopting financial information systems from developed countries rather than market-driven approaches provided by international organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies (e.g., Grossi et al., 2023; Hopper et al., 2017) have demonstrated that the existing literature has primarily focused on the development discourses of public sector accounting systems promoted by international organizations and dominantly reviewed these systems designed by English‐speaking countries and Europe over the past decades. In most cases, international organizations such as the World Bank have received significant scholarly attention, particularly in the context of the adoption of public sector accounting technologies by emerging economies.…”
Section: Introductionmentioning
confidence: 99%